2017
DOI: 10.1007/s40744-017-0087-x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Medical Record Review of Utilization Patterns and Medical Resource Use Associated with Repository Corticotropin Injection among Patients with Rheumatologic Diseases in the United States

Abstract: Introduction: Repository corticotropin injection (RCI) has anti-inflammatory and immune-modulatory effects and is approved for multiple indications, including several rheumatologic conditions. The aims of this nationally representative, retrospective, observational study were to describe patient characteristics, RCI treatment patterns, and barriers to RCI use in patients with rheumatologic disease, and to compare medical resource use (MRU) before and after RCI therapy. Methods: A random sample of US physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…After getting approval (Reference Number: 2020-104) from the Institutional Review Board of the First Affiliated Hospital, Zhejiang University School of Medicine (FAHZJU) and acquiring written informed consent (for participation and publication) from all patients involved, in accordance with the Helsinki Declaration of 1975 and its later amendments, we retrieved medical records of adult patients who were hospitalized at the Qingchun, Chengzhan, and Zhijiang divisions of FAHZJU with the diagnosis of DM, PM, or ADM from December 2010 to November 2019. The inclusion criteria of this study were: (1) age over 18 years old; (2) the diagnosis of DM, PM, or ADM that satisfied the 2017 ACR/EULAR classification criteria [13,14]; (3) international Statistical Classification of Diseases, 10th revision (ICD-10)-coded discharge diagnosis of community-acquired pneumonia (CAP), hospital-acquired pneumonia (HAP), pulmonary fungal infection, and pulmonary infection. Exclusion criteria were: (1) overlap syndromes with other CTDs; (2) hospitalization for reasons unrelated to myositis and its complications, such as fracture, pregnancy, acquired immunodeficiency syndrome, and cataract, etc.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…After getting approval (Reference Number: 2020-104) from the Institutional Review Board of the First Affiliated Hospital, Zhejiang University School of Medicine (FAHZJU) and acquiring written informed consent (for participation and publication) from all patients involved, in accordance with the Helsinki Declaration of 1975 and its later amendments, we retrieved medical records of adult patients who were hospitalized at the Qingchun, Chengzhan, and Zhijiang divisions of FAHZJU with the diagnosis of DM, PM, or ADM from December 2010 to November 2019. The inclusion criteria of this study were: (1) age over 18 years old; (2) the diagnosis of DM, PM, or ADM that satisfied the 2017 ACR/EULAR classification criteria [13,14]; (3) international Statistical Classification of Diseases, 10th revision (ICD-10)-coded discharge diagnosis of community-acquired pneumonia (CAP), hospital-acquired pneumonia (HAP), pulmonary fungal infection, and pulmonary infection. Exclusion criteria were: (1) overlap syndromes with other CTDs; (2) hospitalization for reasons unrelated to myositis and its complications, such as fracture, pregnancy, acquired immunodeficiency syndrome, and cataract, etc.…”
Section: Patientsmentioning
confidence: 99%
“…[ 1 , 2 ]. Dermatomyositis (DM), polymyositis (PM), and the newly recognized amyopathic dermatomyositis (ADM) are common subtypes of IIM in clinical practice [ 2 , 3 ]. IIM has considerable impact on patients’ well-being and quality of life [ 4 ], and the survival of IIM patients is far from optimistic.…”
Section: Introductionmentioning
confidence: 99%
“…A health insurance claims study by Desai et al reported that younger age, residence in the southern United States, being cared for by a rheumatologist, and having a health plan with more generous prescription drug benefits positively impacted treatment initiation with TNF inhibitors [24]. A medical chart review study by Nelson et al found that patients with RA had received an average of 3.6 RA medications before initiating RCI, suggesting that RCI is administered primarily as a late-line therapy [16], which is supported by our findings of high nontraditional DMARD use in these patients. An analysis of 1998-2006 patient-reported data in the US Arthritis, Rheumatism and Aging Medical Information System database concluded that greater disability in the previous 6 months and previous use of glucocorticoids and DMARDs were independent positive predictors of initiation of treatment with biologics for patients with RA, whereas older age and lower annual income were independent predictors of decreased use of biologics [45].…”
Section: Discussionmentioning
confidence: 99%
“…Repository corticotropin injection (RCI; Acthar ® Gel, Mallinckrodt ARD LLC, Bedminster, NJ, USA)—a naturally sourced complex mixture of adrenocorticotropic hormone analogs and other pituitary peptides—is indicated for short-term administration in patients experiencing acute episodes or exacerbations of RA [ 15 ]. Evidence from previous studies suggests that in clinical practice, RCI is used primarily as late-line therapy to treat flares, as a bridge to new therapy, or as an add-on to prior therapy [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 15 , 20 Patients with RA or systemic lupus erythematosus who received RCI had lower rates of hospitalization, emergency department visits and outpatient services. 17 , 19 …”
Section: Introductionmentioning
confidence: 99%